Primary Biliary Neuroendocrine Tumors: A Systematic Review of Surgical Management, Oncologic Outcomes and Implications for Personalized Care - Anna Paspala; Dimitrios K. Vlachos; Dionysios Prevezanos; Panagiotis Dorovinis; Nikolaos Machairas; Stylianos Kykalos; Evangelos Tagkalos; Georgios C. Sotiropoulos (Journal of Personalized Medicine, 2026)
Background/Objectives: Primary biliary neuroendocrine tumors (PBilNETs) are exceptionally rare biliary tract neoplasms that are frequently misdiagnosed preoperatively as cholangiocarcinoma because of overlapping clinical and radiological findings. This systematic review aimed to summarize overall evidence regarding presentation, diagnostic evaluation, surgical management, and outcomes of PBilNETs. Methods: A systematic search of PubMed, Scopus, and Embase databases was performed according to PRISMA guidelines for studies published between January 2000 and December 2025. Studies including adult patients with histologically confirmed and surgically treated PBilNETs were eligible. Data regarding demographics, symptoms, imaging findings, surgical treatment, histopathology, immunohistochemistry, and outcomes were extracted and analyzed. Results: Fifty-eight studies involving 79 patients met the inclusion criteria. Median age at diagnosis was 49 years, with female predominance. Obstructive jaundice, abdominal pain, and pruritus were the most common presenting symptoms. Most tumors originated from the hilar or extrahepatic bile ducts. Preoperative diagnosis was challenging, as most lesions were initially considered cholangiocarcinomas. Surgical resection was the main therapeutic approach and included bile duct excision with biliary reconstruction, pancreaticoduodenectomy, or hepatic resection according to tumor location. Histopathological analysis demonstrated predominantly well- or moderately differentiated neuroendocrine neoplasms with frequent chromogranin A and synaptophysin positivity. Favorable long-term outcomes were reported, with high postoperative survival and limited recurrence during follow-up. Conclusions: PBilNETs remain diagnostically challenging because of their rarity and nonspecific presentation; however, they appear to exhibit a less aggressive biological behavior than conventional biliary adenocarcinomas. Surgical resection remains the cornerstone of treatment, while further multicenter studies are required to optimize diagnostic and therapeutic strategies. The findings also support an individualized multidisciplinary approach integrating clinical presentation, advanced imaging, histopathological grading, and immunohistochemical profiling to optimize personalized management of these rare tumors.